Upper Arm Composition as an Indicator of Body Composition and Nutritional Status of Adolescent Boys Aged 10-18 Years - Sen, Jaydip; Mondal, Nitish; Ghosh, Partha (Journal of Nepal Paediatric Society, 2016)
Introduction: The upper arm composition is usually assessed based on total upper arm area (TUA), upper arm muscle area (UMA), upper arm fat area (UFA) and arm fat index (AFI). It is closely associated with assessment of body composition and nutritional status. The present study aims to determine the age specific variations in upper arm composition and its usefulness in the assessment of body composition and nutritional status among adolescent boys. Materials and Methods: The study was conducted among 964 boys (aged 10 – 18 years) and belonging to the indigenous Rajbanshi population of West Bengal, India. The boys were selected from five different sub-urban government secondary schools located under Siliguri subdivision of Darjeeling district, West Bengal, India. The anthropometric measurements of height, weight, MUAC and TSF were recorded and upper arm composition was estimated based on TUA, UMA, UFA and AFI using standard procedures. The overall body composition was evaluated using body mass index (BMI). Results: There appears to be existence of significant age-specific variations in BMI, UMA and UFA as the boys approached higher ages. The age specific means of TUA, UMA and UFA increased with age. The adolescent boys were observed to be well below the 50th percentiles of the reference population in BMI, TUA, UMA, UFA and AFI. Age and sex-specific smooth percentile curves were derived for height, weight, TSF, BMI, UMA and UFA using the L, M and S modelling approach for further evaluation of body composition. Conclusion: The present study recommends the assessment of body composition and nutritional status to improve screening of nutritional status using upper arm composition, especially in community settings so as to accurately identify the risk of lower or greater adiposity and muscularity, and thereby proposing a major opportunity to improve health through proper intervention programmes. J Nepal Paediatr Soc 2015;35(2):152-161